การพัฒนาตัวบ่งชี้สมรรถนะของผู้บริหารสถานศึกษาของรัฐระดับมัธยมศึกษา สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - เยาวณี เสมา (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purposes of this research were (1) to develop indicators for the competency of the public secondary school administrators under The Office of Basic Education Commission, based on the position standard, an academic standard and personal characteristics of school administrators (2) to survey the competency of the state secondary school administrators under The Office of Basic Education Commission. The public secondary school administrators under The Office of Basic Education Commission were randomly drawn from 406 schools. The instruments used in this study were questionnaire. The subjects were an assistant and planning chief in the schools. Data were analyzed through descriptive statistics, i.e. frequencies, means, standard diviations and One-Way ANOVA. The results were as follows: (1) The indicators for the competency of the public secondary school administrators under The Office of Basic Education Commission were characterized into 78 indicators, i.e. 26 knowledge indicators, 26 skill indicators and 26 personal characteristic indicators. (2) The results of the survey of the competency of the public secondary school administrators under The Office of Basic Education Commission revealed that the overall competency of state secondary school administrators were at high level. Among the three aspects of competency survey, knowledge competency ranked first, while those of personal characterlistic competency and skill competency ranked second and third, respectively. The highest competency resulted was the communication skill while the least competency was the skill of transferring a duty